Hunting caribou subsistence hunting along the northern edge of the boreal forest - Sharp, Henry S. 1944-; Sharp, Karyn (Univ. of Nebraska Press, 2015)
"Denesuline hunters range from deep in the boreal forest far into the tundra of northern Canada. Henry S. Sharp, a social anthropologist and ethnographer, spent several decades participating in fieldwork and observing hunts by this extended kin group. His daughter, Karyn Sharp, who is an archaeologist specializing in First Nations Studies and is Denesuline, also observed countless hunts. Over the years the father and daughter realized that not only their personal backgrounds but also their disciplinary specializations significantly affected how each perceived and understood their experiences with the Denesuline. In Hunting Caribou, Henry and Karyn Sharp attempt to understand and interpret their decades-long observations of Denesuline hunts through the multiple disciplinary lenses of anthropology, archaeology, and ethnology. Although questions and methodologies differ between disciplines, the Sharps' ethnography, by connecting these components, provides unique insights into the ecology and motivations of hunting societies. Themes of gender, women's labor, insects, wolf and caribou behavior, scale, mobility and transportation, and land use are linked through the authors' personal voice and experiences. This participant ethnography makes an important contribution to multiple fields in academe while simultaneously revealing broad implications for research, public policy, and First Nations politics"..